2019
DOI: 10.3390/biom9100621
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Chelation: EDTA Tightly Binds Taq DNA Polymerase, MutT and dUTPase and Directly Inhibits dNTPase Activity

Abstract: EDTA is commonly used as an efficient chelator of metal ion enzyme cofactors. It is highly soluble, optically inactive and does not interfere with most chemicals used in standard buffers making EDTA a common choice to generate metal-free conditions for biochemical and biophysical investigations. However, the controversy in the literature on metal-free enzyme activities achieved using EDTA or by other means called our attention to a putative effect of EDTA beyond chelation. Here, we show that EDTA competes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Its structure is flexible when it is unbound and adopts a rigid conformation, while interacting with cations. 45 In general, the complexation between Cr(III) and EDTA is characterized by a low rate of coordination. 46 The slow complexation and the molecular flexibility would allow us to propose that the organic chelator EDTA coordinates with the surfaces of AgNPs and gradually with Cr(III).…”
Section: Resultsmentioning
confidence: 99%
“…Its structure is flexible when it is unbound and adopts a rigid conformation, while interacting with cations. 45 In general, the complexation between Cr(III) and EDTA is characterized by a low rate of coordination. 46 The slow complexation and the molecular flexibility would allow us to propose that the organic chelator EDTA coordinates with the surfaces of AgNPs and gradually with Cr(III).…”
Section: Resultsmentioning
confidence: 99%
“…According to a study conducted by Khosravinia and Ramesha [ 23 ], EDTA concentrations > 11 µg/µL are known to reduce DNA recovery. Beyond chelating, Lopata et al [ 20 ] also showed that EDTA affects enzyme activity by tightly binding to the active site of enzymes such as Taq DNA polymerase, dUTPase, and dNTPase, resulting in low or no PCR products. As an example, Taq polymerase requires Mg 2+ for activation, while EDTA tends to compete with Mg 2+ for binding, resulting in enzyme inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Chelating agents include ethylene diamine tetraacetic acid (EDTA) and ethylene glycol-bis(2-aminoethylether)-N,N,N′,N′-tetraacetic acid (EGTA) [ 10 , 17 ]. EDTA and EGTA have similar properties and can chelate nearly all the same metals, such as Mg 2+ , Cu 2+ , Fe 2+ , Mn 2+ , Ni 2+ , and Zn 2+ ions [ 20 ]. However, the affinity of EDTA and EGTA for magnesium varies, with EDTA having a high affinity and EGTA having a low affinity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its half-life is usually greater than 2 h at 92.5 °C; however, it is still unable to maintain its stability in a solvent (predominantly aqueous solution and some necessary storage buffer) for long storage time at room temperature. 8,9 Therefore, the best way to preserve the enzymatic microstructure and functionality usually involves storing the reagent at a low temperature of approximately −20 °C; this ensures that the enzyme neither loses its function nor reacts with other substances such as the primer, before experiments. 10 To efficiently and accurately carry out PCR tests, the cold chain transportation and storage for the reagents should be seriously considered; however, these pose challenges for some emergency situations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is well known that the Taq polymerase is very sensitive to temperature variation, light intensity, pH value, and so forth. Its half-life is usually greater than 2 h at 92.5 °C; however, it is still unable to maintain its stability in a solvent (predominantly aqueous solution and some necessary storage buffer) for long storage time at room temperature. , Therefore, the best way to preserve the enzymatic microstructure and functionality usually involves storing the reagent at a low temperature of approximately −20 °C; this ensures that the enzyme neither loses its function nor reacts with other substances such as the primer, before experiments …”
Section: Introductionmentioning
confidence: 99%